PENGARUH TINGKAT BUNGA PASAR DAN KARAKTERISTIK OBLIGASI PADA IMBAL HASIL OBLIGASI YANG TERGOLONG INVESTMENT GRADE - Eka Putri, Ni Putu Kartika; Astika, Ida Bagus Putra; Dewi, Ayu Arysta (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Yields of bonds is an important factor for consideration of investors in the purchase of bonds as investment instruments. The purpose of this study was to determine the effect of market interest rates and bond characteristics, namely coupons interest rate and term to maturities on the yield of bonds. This research was conducted at the company that issued the bonds listed in Indonesia Stock Exchange in 2013-2015. The research sample was determined by purposive sampling technique. The sample in this study was 28 bonds from 14 companies. Data analysis technique used is multiple linear regression. The results showed that the variable market interest rates and term to maturities positive effect on bond yields. While variable coupon interest rate has no effect on bond yields
Keywords: bond yields, market interest rates, coupons interest rate, term to maturities